Development of food safety risk assessment tools based on molecular typing and WGS of Campylobacter jejuni genome. (17th September 2019) - ,; Ardelean, AI; Calistri, P; Giovannini, A; Garofolo, G; Di Pasquale, A; Conte, A; MorelliD, D
Abstract: The 'learning‐by‐doing' EU‐FORA fellowship programme in the development of risk assessment tools based on molecular typing and WGS of Campylobacter   jejuni genome was structured into two main activities: the primary one focused on training on risk assessment methodology and the secondary one in starting and enhancing the cooperation between the hosting and home organisations, or other joint activities. The primary activities had three subsequent work packages (WPs): WP1 data organisation, WP2 cluster and association analyses, and WP3 development of risk assessment models. The secondary activities have branched into one workshop and the initiation of a cooperation programme between the hosting and home organisations. In the last quarter, the fellow had contributed to the characterisation of some pathogens in possible response to a changing climate, part of the CLEFSA project. The fellow attended various forms of training: online and on‐site courses, and also participated at several conferences and meetings for improving his knowledge and skills, contributing to performing the Campylobacter risk assessment and source attribution.